CHALLENGES FACING CIVIL AVIATION AT JUBA INTERNATIONAL AIRPORT, JUBA CITY, CENTRAL EQUATORIA STATE - Yor , Dr. Angelo Okic (IJRDO- Journal of Educational Research, 2023)
This study is conducted to discuss the challenges facing Civil Aviation at Juba International airport, Juba City, Central Equatoria State. Moreover, the study concentrated on illustration of Civil Aviation historical background in South Sudan in general. On the same occasion, the paper tried to explain the theories of Civil Aviation. Nevertheless, the study employed the questionnaire for data collection. It also used descriptive method for data analysis. In addition, the study employed the qualitative and quantitative methods in data collection. Also, the study used tables in data analysis, beside the map of Juba city as well as figures of Airplane was employed as materials in the study. On the other hand, the findings of the study found that 94% of respondents affirmed that lack of skills in Civil Aviation safety had contributed to an increase in number of accidents at international airport, Juba City, Central Equatoria State.  In addition, 92% of respondents availed that political instability in South Sudan affected the progress in Civil Aviation at Juba International airport in particular as well as other airports in the country in general. Moreover, the study recommended that Civil Aviation workers should be oriented and train on Civil Aviation safety and equipped them with civil aviation regulations as well as main techniques of specialization. Also, the study recommended for the relocation of the airport because it is based in the area near to the residential sites.